Parental connectedness, monitoring and depression on substance abuse among undergraduate students of the University of Ibadan (2016)
Based on the ever increasing rate of substance abuse among university undergraduates, this study investigated parent connectedness, parental monitoring, and depression on substance abuse among undergraduate students in the University of Ibadan. A descriptive research design of correlational type was adopted for this study. Four reliable measuring scales were used for the data collection. A sample of 220 adolescents was randomly selected among four faculties of the University of Ibadan. The study found a significant relationship among the variables and dependent variable. A significant joint effect of parent connectedness, parental monitoring, and depression to the prediction of substance abuse was established among undergraduate students. The most potent factor was depression; followed by parental monitoring and parent connectedness. This implies that, there is likelihood for an increase in adolescent's engagement HI substance abuse when there is a high influence of depression. While adolescent students may reduce their engagement in substance abuse when parent connectedness and parental monitoring is high. Among others, it was recommended that the school counselling unit should organize relaxation training programmes to reduce the stress and frustration that lead students engaging in substance abuse. More so parents should keep the relationship between them and their children lively and healthy even when they are far away on campus.